Measurement of lower canine clinical crown index in male and female for gender identification - Handayani, Rita Dewi; Ardan, Rachman; Rikmasari, Rasmi (Universitas Padjadjaran, 2007)
The purpose of this research was to acquire the value index of clinical crown lower jaw canine male and female, and to prove whether the index of male's canine is bigger than female's. The samples of the research was the students of Faculty of Dentistry Universitas Padjadjaran class of 1998 until 2001 by using proportional random sampling method according to the criteria and also adjust with the numbers of male and female composition in per class. The characteristic of the research was analytical descriptive with survey technique. The result of t test statistic measurement was that index of clinical crown tower jaw canine of mate was 1.50 and female was 1.21, by using reliance 95%. The inference of the research showed that the index of clinical crown lower jaw canine of male was significantly bigger than female's. The result of the research can be used as auxiliary data from the techniques to process gender identification in odontology forensic.